A note on recent trends in knowledge creation and appropriation through genomics: a scientometric analysis. (1st January 2001) - Looze, Marie-Angele de; Coronini, Roger; Joly, Pierre-Benoit
Using scientometric methods, this paper examines the impact of investment in the field of "genomics". It reveals that in terms of scientific publications and application for patents, the USA is still in the lead, that Japan has caught up well, and that Europe, while being strong in terms of scientific production, is weak in terms of patent applications. As in some of the other high-tech sectors, the European countries are willing to allocate their resources for the advancement of science but industrial development is slow to follow suit. The gap within the different groups of the triad remains important.